V2R communication in internet of vehicles - Xiaoting MA; Junhui ZHAO; Chuanyun WANG; Yiguo XU (Dianxin kexue)
With the tremendous advantages of wireless technologies，it has been put forward higher requirements for intelligent transportation systems（ITS）.Pure Ad Hoc network or V2V communication is not reliable and sufficient for many applications.V2R communication is reliable，safe and comfortable.It can easily and quickly obtain real-time traffic information，because of the cooperation between V2V communication and V2R communication which can achieve the exchange of information between vehicles，drivers，and roads，and improve the convenience and comfort of the trip.Firstly，the characteristics of V2R communication were studied，then the network architecture was introduced.In addition，the connection for V2R communication was analyzed.Finally，the challenges of V2R communication were explored.